The Kahoot! Application in Medical Education : The Effect on Student Motivation and Learning Evaluation Result - Galuh Suryandari; Tias Asih Subagio (Universitas Muhammadiyah Yogyakarta, 2021)
Medical education institutions in Indonesia have similarities in facing challenges in the teaching and learning process with other institutions in Asia. Institutions that set up medical education study programs find it difficult to conduct large or conventional classes with a single lecture method based on separate scientific disciplines between biomedic and non-biomedic medicine (non-biomedic).The main problems that arise are the lack of student activity and student awareness to learn independently. It is necessary to improve the single class lecture.Gamification is a learning medium that increases student engagement by attracting all students The Kahoot! Application reinforcing some effort and desire to engage students,This reasearch aim to measure the effectivity of Kahoot! application on students’ motivation and learning evaluation result between all batches and two medical science division of single lecturer in school of medicine FMHS UMY.This ia a quantitative research with quasi experimental pre-post test design without control. The sample in this study were active students of the Medical Studies Program class of 2017, 2016 and 2015 who were willing to take part in a single lecture process with partner lecturers. Data analized with Wilcoxon test to determine whether there is a significant difference between the results of filling out the MSLQ questionnaire before and after the application of the Kahoot! quiz.In this study, the results obtained based on the Wilcoxon test conducted, that the generation of 2016.2017 and 2018 have p <0.05 so that it can be concluded that the hypothesis states that there are significant differences between Kahoot! (Pre Test) and Learning Evaluation (Post Test) proven.